The Influence of Problem-Based Learning Model Learning Assisted by Science Media Kits on Student Learning Outcomes in Hydrocarbons - Ulfiana Ulfiana; Minarni R. Jura; Tahril Tahril (Universitas Tadulako, 2022)
This study aimed to determine the effect of the problem-based learning model assisted by KIT IPA media on student learning outcomes in hydrocarbon material in class XI IPA SMA N 6 Palu. The type of research used was Pre-experiment with Alternative Treatment design, Post-Test-Only with nonequivalent Groups Design. Sampling was done using the purposive sampling technique with samples consisting of class XI IPA 4 as experimental class I and class XI IPA 2 as experimental class II. The research instruments were the learning outcomes tests, RPP, and observation sheets previously validated in theory and empirically. Testing student learning outcomes used t-test analysis two (two parties) with a prerequisite test: normality and homogeneity tests, then the t-test hypothesis test (two parties) was applied. Based on the research results and analysis of the research data, the value of student learning outcomes in the post-test of the experimental class I was 65.7 and for the exploratory class II was 59.9, while the standard deviation was 10.4 and 9.7, respectively. The results of the statistical testing of hypothesis testing obtained tcount> ttable or 2.60> 1.70 so that H1 was accepted. It means that the learning model of problem-based learning instruction assisted by KIT IPA media affects the learning outcomes of students of SMA Negeri 6 Palu.